Abrocitinib: A New FDA-Approved Drug for Moderate-to-Severe Atopic Dermatitis. Issue 1 (January 2023) - Perche, Patrick O.; Cook, Madison K.; Feldman, Steven R.
Objective: The objective of this article is to review abrocitinib, an oral Janus kinase (JAK) 1 inhibitor, for the treatment of patients with moderate-to-severe atopic dermatitis (AD). Data Sources: A literature search of MEDLINE (PubMed) was performed for articles from inception through end-March 2022 using the following search terms: atopic dermatitis, abrocitinib, PF-04965842, methotrexate, cyclosporine, dupilumab, ruxolitinib, and JAK-STAT pathway. Study Selection and Data Extraction: English articles relating to pharmacology, pharmacokinetics, efficacy, and safety of abrocitinib, and other conventional systemic medications for AD, were included. Data Synthesis: Across phase IIb and phase III clinical trials, abrocitinib was efficacious with an average of 47.5% patients on 200 mg abrocitinib and 32.0% on 100 mg abrocitinib achieving an Investigator's Global Assessment (IGA) of 0 or 1 at 12 weeks. In comparison with dupilumab 300 mg subcutaneously every other week, patients on abrocitinib 200 mg once daily had improved disease severity and itch response. The majority of adverse events were not severe and self-limited. Relevance to Patient Care and Clinical Practice: Prior to Food and Drug Administration (FDA) approval of abrocitinib, prednisone was the only FDA-approved oral medication for AD. Although biologics such as dupilumab have revolutionized care, some patients prefer oral medications. Compared with clinical trials of conventional AD treatments, abrocitinib appears more effective. Conclusions: Abrocitinib is an efficacious oral JAK 1 inhibitor recently FDA-approved for patients ≥ 18 years old with moderate-to-severe AD who have not responded to systemic medications or when contraindicated otherwise.